Comparative pathogenomics of Clostridium tetani. - Jonathan E Cohen; Rong Wang; Rong-Fong Shen; Wells W Wu; James E Keller (PLoS ONE)
Clostridium tetani and Clostridium botulinum produce two of the most potent neurotoxins known, tetanus neurotoxin and botulinum neurotoxin, respectively. Extensive biochemical and genetic investigation has been devoted to identifying and characterizing various C. botulinum strains. Less effort has been focused on studying C. tetani likely because recently sequenced strains of C. tetani show much less genetic diversity than C. botulinum strains and because widespread vaccination efforts have reduced the public health threat from tetanus. Our aim was to acquire genomic data on the U.S. vaccine strain of C. tetani to better understand its genetic relationship to previously published genomic data from European vaccine strains. We performed high throughput genomic sequence analysis on two wild-type and two vaccine C. tetani strains. Comparative genomic analysis was performed using these and previously published genomic data for seven other C. tetani strains. Our analysis focused on single nucleotide polymorphisms (SNP) and four distinct constituents of the mobile genome (mobilome): a hypervariable flagellar glycosylation island region, five conserved bacteriophage insertion regions, variations in three CRISPR (clustered regularly interspaced short palindromic repeats)-Cas (CRISPR-associated) systems, and a single plasmid. Intact type IA and IB CRISPR/Cas systems were within 10 of 11 strains. A type IIIA CRISPR/Cas system was present in two strains. Phage infection histories derived from CRISPR-Cas sequences indicate C. tetani encounters phages common among commensal gut bacteria and soil-borne organisms consistent with C. tetani distribution in nature. All vaccine strains form a clade distinct from currently sequenced wild type strains when considering variations in these mobile elements. SNP, flagellar glycosylation island, prophage content and CRISPR/Cas phylogenic histories provide tentative evidence suggesting vaccine and wild type strains share a common ancestor.